Fantastic feeders - Knight, Tim. (Oxford : Heinemann Library, 2003)
Explores different kinds of food eaten by certain animals and the special teeth or other tools they have for eating that food, as well as some of the ways plants avoid being eaten.
The giant restaurant -- Plant food -- Eat your greens -- Plants bite back -- A sweet tooth -- Fruit and nut cases -- Insect collectors -- Helping each other -- Blood suckers -- Big eaters -- Predators -- Nature's vacuum cleaners -- Fact file.
Includes index.
Keywords: Animals -- Food; Food chains; Plant defences